Qur’an and Sasak Culture Tafsir on Religious Attitudes in Lombok - Saladin, Bustami (Institut Agama Islam Negeri Madura, 2019)
One of the traditions still preserved on the island of Lombok is the tradition of using Berugaq as a place to study or recite the Koran. Berugaq is a place to receive guests, family deliberations, a place for worship, and even a place for learning and discussion to provoke and motivate residents to learn the Quran and Tafsir. Berugaq is an alternative because, in addition to a comfortable position, Berugaq is an alternative. After all, in addition to a comfortable home and being in the open air. Berugak is also made a gathering place that symbolizes kinship. In Berugaq, the Al-Qur’an is submitted as an interpretation of religious attitudes because Berugaq is considered comfortable and can motivate residents to participate in learning the Al-Qur’an and its performance. Explanations of Al-Qur’an verses are primarily done in mosques and schools, never in Berugaq or Langgar, which makes the researcher interested in this study. Teaching methods of interpreting the Al-Qur’an by explaining the content of the verses of the Al-Qur’an with discussion and question and answer. The method used in this research is a qualitative research method descriptive analytical approach by applying a systematic, directed, and accountable way of working. With the learning model in Berugaq, community members are motivated to learn the Al-Qur’an because they consider Berugaq to be a comfortable and attractive place where more and more people, both youth and children who participate in learning the Qur’an so that the traditional learning in Berugaq is a tradition that needs to be developed and preserved.